Analysis of TMT heterogeneity and IPO underpricing of listed companies in the low carbon economy sector: Evidence from China’s stock market - Zhou, Xiaohua; Feng, Guan; Ren, Yong (Frontiers in Energy Research, 2023)
Introduction: Issuance pricing is an important part of the operation of the securities market. Its pricing is directly related to the interests of issuers, investors and underwriters, as well as the regulatory and resource allocation functions of the securities issuance market. When the industry expectations vary greatly, the company has greater TMT heterogeneity. When the market expectation gap expands, the possibility of risk conversion increases. IPO underpricing occurs in stocks of developed countries, developing countries and emerging countries. Because the issuer and the underwriter investors have different information, for example, the information advantage of the underwriter will bring risks to investors when purchasing IPO shares. IPO underpricing is a compensation for the risks brought by information asymmetry. Methods: At present, little attention has been paid to how the value of listed companies affects the underpricing of intellectual property. This paper will fill in this gap and empirically study the impact of management ability of senior management team on IPO underpricing. Therefore, starting from the Chinese stock market, this paper studies the evidence of vertical parallel executives, heterogeneity of senior management team and IPO underpricing. Results: The average values of NCSKEW (C1) and DUVOL (C2) were −0.301 and −0.203, respectively, which were close to the descriptive statistics of the study. Discussion: The dependent variable data in this paper has certain reliability. The minimum value of NCSKEW is −0.361 and the maximum value is 0.392, indicating that the fragmentation risk of different stocks is relatively high.